Letters - Richardson, Henry Handel, 1870-1946.; Hoult, Norah, 1901-1984. (1931)
Five letters from H. H. Richardson to Miss Norah Hoult (author of Holy Ireland and Time, Gentlemen Time).
Manuscript reference no. : NLA MS 5770.
Keywords: Richardson, Henry Handel, -- 1870-1946 -- Correspondence; Hoult, Norah, -- 1901-1984 -- Correspondence; Authors, Australian -- Correspondence; Novelists, Australian -- Correspondence